Consumers' attitudes towards sonic logos - Shi, Qichao (2012)
Sonic logos are increasingly being used as a way of sonic branding in marketing activities. Scholars have acknowledged the benefits of sonic logos, such as communicating brand attributes to consumers. However, studies about consumers’ attitudes towards sonic logos are scarce. This paper examined consumers’ attitudes towards sonic logos, particularly how cognitive and affective elements correlated with such attitudes, whether such attitudes had correlations with consumers’ attitudes towards the associated brands of sonic logos, and whether such attitudes had relationships with consumers’ purchase intentions towards the associated brands of sonic logos. Through a PowerPoint-assisted questionnaire, data were collected from 78 Chinese students who were from the University of Nottingham, Ningbo, China. With the help of SPSS, it was found that consumers’ attitudes towards sonic logos were close to positive; both cognitive elements (a consumer’s perception of attractiveness of a sonic logo, a consumer’s perception of uniqueness of a sonic logo, a consumer’s perception of fitness for its brand of a sonic logo) and affective elements (a consumer’s perception of emotionality of a sonic logo, a consumer’s perception of activation of emotional memories of a sonic logo, a consumer’s perception of pleasure of a sonic logo) had positive relationships with consumers’ attitudes towards it; and a consumer’ attitude towards the sonic logo had positive relationships with her/his attitude towards the associated brand of the sonic logo and with her/his purchase intention towards the associated brand of the sonic logo. These findings not only could contribute to understanding that how sonic logos were perceived in consumers’ minds, but also to some extent could help marketing practitioners make better decisions about whether to implement sonic logos or not and how to design good sonic logos.